ANALISIS KOMPARASI PENGHITUNGAN KEUNTUNGAN PEMBIAYAAN PERUMAHAN ANTARA BANK KONVENSIONAL DAN BANK SYARIAH - Salihah Khairawati; Sugeng Widodo (At-Tauzi : Jurnal Ekonomi Islam, 2022)
The purpose of this research is to analyze whether there are differences in the calculation of profit margins used in conventional banks and Sharia banks related to housing financing. There are three methods that usually used in almost all banks consist of effective methods, annuities and flat, as well as contracts Murabahah in sharia banks. The design of this research is a qualitative study using comparative descriptive methods for analyzing data. Comparison analysis is done to see if there is a comparison between calculation method of profit margin financing of conventional bank and the financing of Murabahah sharia banks. Results found that conventional banks used a flat method to calculate interest income in housing credit financing contract. While Sharia Bank calculates profit margin from buy and sell transactions with a murabahah contract with flat method. This means there is no difference in the method of calculating profit margins between sharia banks and conventional banks.